Effect of anterior mobilization and shortening in the correction of rigid idiopathic thoracic scoliosis - Ruf, Michael; Letko, Lynn; Matis, Nora; Merk, Harry R.; Harms, Jürgen (Spine, 2013)
Study Design. Retrospective study of patients with anterior release and posterior correction instrumentation in a 2-stage procedure for rigid thoracic scoliosis. Objective. To examine the effect of the anterior release and shortening alone as well as its role in the overall correction. Summary of Background Data. With segmental transpedicular instrumentation the need for an additional anterior mobilization became rare. However, its effect on sagittal profile was not sufficiently acknowledged. - Methods. Twenty-two patients with rigid thoracic scoliosis (Lenke 1A, n = 3; 2A, n = 6; 2B, n = 2; 2C, n = 1; 4B, n = 1; 4C, n = 9 patients) were operated in a 2-stage procedure with anterior release followed by posterior correction. The anterior release included convex resection of the rib heads and shortening of the anterior column by resection of the discs and the convex anterolateral endplates in a mean of 8 (4-11) segments. After 14 days (6-27), the posterior instrumentation and correction was done. Results. The preoperative thoracic scoliosis measured a mean of 80°, upper thoracic 42°, and lumbar 49°. The thoracic curve corrected in bending 20° (25%), upper thoracic 10° (24%), and lumbar 26° (53%). The mean thoracic kyphosis (T5-T12) was 11°, lumbar lordosis was −41°. After the anterior release and shortening, thoracic scoliosis improved to 50°, thoracic kyphosis increased to 32°. After the posterior surgery the following values were noted: thoracic scoliosis 10°, upper thoracic 9°, lumbar 8°, thoracic kyphosis 25°, and lumbar lordosis −41°. The results were maintained at follow-up. Conclusion. Anterior shortening results in a spontaneous correction of the thoracic scoliosis and hypokyphosis. In this series, the Cobb angle reduced 38% from a mean of 80° to a mean of 50°. Thoracic kyphosis increased from 11° to 32°. This correction was achieved without any corrective force or instrumentation. The second-stage posterior correction is facilitated and nearly complete correction is achieved with a residual curve on average of 10° with a physiological sagittal profile. Level of Evidence: 4
Gesehen am 24.01.2022